2015
DOI: 10.1016/s1474-4422(14)70318-7
|View full text |Cite|
|
Sign up to set email alerts
|

Eplerenone for early cardiomyopathy in Duchenne muscular dystrophy: a randomised, double-blind, placebo-controlled trial

Abstract: Summary Background Cardiomyopathy is a leading cause of death in patients with Duchenne muscular dystrophy and myocardial damage precedes decline in left ventricular systolic function. We tested the efficacy of eplerenone on top of background therapy in patients with Duchenne muscular dystrophy with early myocardial disease. Methods In this randomised, double-blind, placebo-controlled trial, boys from three centres in the USA aged 7 years or older with Duchenne muscular dystrophy, myocardial damage by late … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
184
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 195 publications
(189 citation statements)
references
References 34 publications
1
184
0
4
Order By: Relevance
“…253 A subsequent randomized, placebocontrolled trial of boys and young men with DMD treated with background ACEI or ARB found that the addition of eplerenone resulted in better preservation of LV circumferential strain measured by CMR. 254 Although it is well known that hyperkalemia is a side effect of aldosterone blockade, and potassium levels must be monitored in patients taking aldosterone antagonists, no hyperkalemia was noted in this trial. 248,249,254 A noninferiority trial is ongoing to compare spironolactone and eplerenone in boys and young men with DMD.…”
Section: Mineralocorticoid Antagonistsmentioning
confidence: 75%
See 1 more Smart Citation
“…253 A subsequent randomized, placebocontrolled trial of boys and young men with DMD treated with background ACEI or ARB found that the addition of eplerenone resulted in better preservation of LV circumferential strain measured by CMR. 254 Although it is well known that hyperkalemia is a side effect of aldosterone blockade, and potassium levels must be monitored in patients taking aldosterone antagonists, no hyperkalemia was noted in this trial. 248,249,254 A noninferiority trial is ongoing to compare spironolactone and eplerenone in boys and young men with DMD.…”
Section: Mineralocorticoid Antagonistsmentioning
confidence: 75%
“…254 Although it is well known that hyperkalemia is a side effect of aldosterone blockade, and potassium levels must be monitored in patients taking aldosterone antagonists, no hyperkalemia was noted in this trial. 248,249,254 A noninferiority trial is ongoing to compare spironolactone and eplerenone in boys and young men with DMD. Although these early results are promising, the relatively short duration of follow-up and the lack of confirmatory studies make their long-term benefit unknown.…”
Section: Mineralocorticoid Antagonistsmentioning
confidence: 75%
“…In this context, Raman et al 48 presented a positive placebo-controlled randomized trial in 42 DMD boys from three US centers treated with eplerenone (Pfizer Inc.) or placebo in association with steroids and on a background of ACE inhibitors or angiotensin receptor blockers. Eplerenone works by blocking the hormone aldosterone (and the aldosterone receptor), and, because it lowers the amount of sodium and water retained in the body, it is used as a diuretic in many cardiac conditions.…”
mentioning
confidence: 99%
“…Significantly decreased left ventricular circumferential strain as a primary outcome was found on cardiac magnetic resonance imaging. 48 A longer follow-up would be necessary to determine if the combination of eplerenone and other cardioprotective treatments results in prolonged survival. Another potential limitation of this trial is the relative small cohort of patients, but in a disorder like DMD it is difficult to recruit adequate numbers of patients and perform blinded cardiac magnetic resonance imaging studies.…”
mentioning
confidence: 99%
See 1 more Smart Citation